1986
DOI: 10.1159/000262232
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Tissue Biopsy: Techniques and Indications

Abstract: A considerable variety of invasive intrauterine procedures has been developed in the last 15 years. This article describes techniques for obtaining fetal blood, skin, liver, tumour specimens and chorionic villi, and discusses their indications and risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…In 1986, the same group described an US-guided biopsy of an intrapulmonary mass, using a 16G needle. A congenital pulmonary adenomatoid malformation (CPAM) of the lung was diagnosed on histological examination and an abortion was performed [2] .…”
Section: Discussionmentioning
confidence: 99%
“…In 1986, the same group described an US-guided biopsy of an intrapulmonary mass, using a 16G needle. A congenital pulmonary adenomatoid malformation (CPAM) of the lung was diagnosed on histological examination and an abortion was performed [2] .…”
Section: Discussionmentioning
confidence: 99%
“…An electron microscope study of the fetal skin sample is required to confirm the diagnosis. The procedure is safe and in a study of 52-skin biopsy by Rodeck no complications were recorded [39].…”
Section: Technique Of Fetal Skin Biopsymentioning
confidence: 91%
“…It has been reported that fetal skin (Golbus et al, 1980), fetal liver (Rodeck et al, 1982), and fetal muscle (Evans et al,199 1) can be useful for early prenatal diagnosis of a number of fetal diseases. Rodeck and Nicolaides (1986) briefly reported on fetal lung biopsy in a case of CCAML. They obtained their specimen by aspiration biopsy.…”
Section: Discussionmentioning
confidence: 99%